Effect of intralitter size on 60 and 95 day fetal myogenesis and development in the pig - Feldpausch, Julie Ann (Kansas State University, 2015)
Piglet birth weight (BtW) is inextricably associated with preweaning survival. The non-linear antagonistic relationship between BtW and mortality risk is more severe in pigs <1.11 kg BtW than in pigs with BtW >1.11 kg. Thus, our research categorized fetal pigs as small (SM), median (MD), or large (LG) size depending on relative crown-rump length at d-60 gestation or BW within litter at d-95 gestation to evaluate differences in fetal myogenesis and development. At both d-60 and d-95, brain weights did not differ but brain weight:liver weight ratio was larger (P<0.05) for SM compared MD and LG. Cross-sectional area of the Longissimus muscle increased with increasing fetal size so that LG and MD had larger (P<0.05) whole muscle cross-sectional areas than SM although number of primary and relative secondary muscle fibers and their respective cross-sectional areas did not differ. Day-60 mRNA abundance of both IGF-1 and IGF-2 in SM was greater (P<0.05) than in MD and LG. Fetal size had a marginally significant effect (P=0.103) on gene expression of IGF-2 receptor with expression least in LG. Small fetuses had greater (P<0.05) d-60 MyoD gene expression and d-95 serum IGF-1 levels than MD and LG. Two experiments were conducted to determine the effects of feeding low or high doses of chlortetracycline (CTC) and antibiotic alternatives (pharmacologic Zn, Cu, and essential oil), alone or in combination, on nursery pig growth performance. Pharmacologic Cu (125 ppm from CuSO[subscript]4), Zn (2,000-3,000 ppm from ZnO), or increasing CTC level (0-441 ppm) improved growth performance additively while Origanum essential oil (0.005%) elicited no benefits and decreased G:F. Interactive effects of supplemental Cu (125 ppm), Zn (150 ppm), and ractopamine HCl (10 ppm for 28 d) on finishing pig growth performance, carcass characteristics, and antimicrobial susceptibility of enteric bacteria was evaluated. Ractopamine increased (P<0.001) ADG, G:F, HCW, percentage carcass yield, loin depth, percent fat-free lean, and decreased (P=0.014) backfat. Copper and/or Zn did not improve ADG, ADFI, or carcass traits. Fecal E. coli and Enterococcus bacterial resistance to most antibiotics decreased (P<0.05) over time or was stable for those that had a low baseline percentage of resistance.
Keywords: Pig; Fetus; Myogenesis; Mineral; Essential oil; Antibiotic resistance; Agriculture, General (0473); Animal Sciences (0475); Biology, Animal Physiology (0433)